Wykroczenia na tle seksualnym w listach św. Hieronima - Gburek, Andrzej (Vox Patrum, 2009)
The author of the article: „The problem of sexual offences, as a result of the mystery of iniquity present in the world, in the light of St. Jerome’s letters”, shows paradox of human existence, in which men, as a real being, continually escapes into the world of dreams and utopia; as a social being, adores in himself anarchistic behaviors; moral and religious values are precious for him, however by the whole of his existence opposes them; he speaks about the ideals of truth, justice and love, but in practice uses false in the wide sense of this word, without difference of time in which he lives and systems under which he exists.